Introduction to ship operations and onboard safety - Olsen, Alexander Arnfinn (Routledge, 2022)
"This textbook is an introduction in the maritime industry that is appropriate for students and professionals. It covers shipboard safety organisation, inductions and new crew member familiarisation, safe means of access to enclosed spaces, risk assessment and risk management, and specific hazardous activities"--
Includes index.
Keywords: Merchant marine -- Handbooks, manuals, etc; Merchant marine -- Great Britain; Seamanship -- Handbooks, manuals, etc